Question

\[ \text{Find } 2011^2 - 2010^2 \text{?} \]

Ask by Zimmerman Warner. in Turkey
Feb 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Sonuç: 4021

Solution

Verilen ifadeyi şu şekilde sadeleştirebiliriz: a² - b² = (a - b)(a + b) Burada a = 2011 ve b = 2010 olduğuna göre: 2011² - 2010² = (2011 - 2010)(2011 + 2010) = 1 × 4021 = 4021 Sonuç: 4021

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Did you know that the difference of squares can make your calculations a breeze? You can use the formula \(a^2 - b^2 = (a-b)(a+b)\). For this problem, let \(a = 2011\) and \(b = 2010\). So, you have \(2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) = 1 \times 4021 = 4021\). Now, here’s a fun fact: this method can be applied to any pair of consecutive numbers! No need to calculate each square individually—just plug in your numbers and you’re golden!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy